MENANAMKAN JIWA KEBANGSAAN PADA SANTRI AN NUR TOMPOBULU GUNA MENANGKAL PAHAM ISLAMOPHOBIA - Marlina Siri (CV. ADIBA AISHA AMIRA, 2022)
This research aims to instill a soul of love towards the Unitary State of the Republic of Indonesia (NKRI) in every santri, as well as to know the role of santri against the understanding of Islamophobia that develops during the development of pesantren. The research discusses the national insight that is the Indonesian nation's perspective on themselves and their environment prioritizes the unity and unity of the nation and the unity of the region based on Pancasila, the Constitution of the Republic of Indonesia in 1945, Bhineka Tunggal Ika and the Unitary State of the Republic of Indonesia (NKRI). This research uses qualitative methodology. Subjective views emphasize the creation of meaning, meaning that individuals make use of all behaviors that occur. The conclusion of the study is to make santri a national bulwark of the struggle against Islamophobia. They are forged to have a sense of responsibility in seeing the reality of colonization, including counteracting Islamophobia. The position occupied by santri after becoming alumni of pesantren is increasingly positive. Santri became a graduate who played a lot in social life and nationality and began to take roles in public positions. Ustadz or caregiver always instills the soul of obstetrics and how to contribute to the nation and state. Ustadz and the teacher also should rebuke and remind santri who often carry teachings or understandings that are contrary to the teachings of Islam. The study recommends to the relevant parties to include material hazards that develop contrary to the values of Pancasila.